The role of L-3-1-123-iodine-α-methyl tyrosine-SPECT in cerebral gliomas - Weckesser, M.; Schmidt, D.; Matheja, P.; Coenen, H. H.; Langen, K.-J. (Nuklearmedizin - NuclearMedicine, 2000)
L-3-1-123-iodine-a-methyltyrosine (IMT) is a 1-123-labelled amino acid which has been used for single photon emission computed tomography (SPECT) of cerebral gliomas for more than a decade. IMT-SPECT is able to detect tumor infiltration independent of disruptions of the blood-brain barrier which is often difficult with computed tomography or magnetic resonance tomography. The method is useful to detect tumor recurrences and helps to distinguish gliomas from non-neoplastic brain masses. IMT-SPECT is thus a valuable tool in the diagnostic evaluation and in therapy planning of patients with cerebral gliomas.
Keywords: Brain tumor; glioma; scintigraphy; amino acid; SPECT